Sizing of a fuel cell–battery backup system for a university building based on the probability of the power outages length. (November 2022) - Rodriguez, Rusber; Osma, German; Bouquain, David; Solano, Javier; Ordoñez, Gabriel; Roche, Robin; Paire, Damien; Hissel, Daniel
Abstract: Hydrogen is a bright energy vector that could be crucial to decarbonise and combat climate change. This energy evolution involves several sectors, including power backup systems, to supply priority facility loads during power outages. As buildings now integrate complex automation, domotics, and security systems, energy backup systems cause interest. A hydrogen-based backup system could supply loads in a multi-day blackout; however, the backup system should be sized appropriately to ensure the survival of essential loads and low cost. In this sense, this work proposes a sizing of fuel cell (FC) backup systems for low voltage (LV) buildings using the history of power outages. Historical data allows fitting a probability function to determine the appropriate survival of loads. The proposed sizing is applied to a university building with a photovoltaic generation system as a case study. Results show that the sizing of an FC–battery backup system for the installation is 7.6% cheaper than a battery-only system under a usual 330-minutes outage scenario. And 59.3% cheaper in the case of an unusual 48-hours outage scenario. It ensures a 99% probability of supplying essential load during power outages. It evidences the pertinence of an FC backup system to attend to outages of long-duration and the integration of batteries to support the abrupt load variations. This research is highlighted by using historical data from actual outages to define the survival of essential loads with total service probability. It also makes it possible to determine adequate survival for non-priority loads. The proposed sizing is generalisable and scalable for other buildings and allows quantifying the reliability of the backup system tending to the resilience of electrical systems.